If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(3c + 2) + 4(2c + 1) = 0 Reorder the terms: 5(2 + 3c) + 4(2c + 1) = 0 (2 * 5 + 3c * 5) + 4(2c + 1) = 0 (10 + 15c) + 4(2c + 1) = 0 Reorder the terms: 10 + 15c + 4(1 + 2c) = 0 10 + 15c + (1 * 4 + 2c * 4) = 0 10 + 15c + (4 + 8c) = 0 Reorder the terms: 10 + 4 + 15c + 8c = 0 Combine like terms: 10 + 4 = 14 14 + 15c + 8c = 0 Combine like terms: 15c + 8c = 23c 14 + 23c = 0 Solving 14 + 23c = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + 23c = 0 + -14 Combine like terms: 14 + -14 = 0 0 + 23c = 0 + -14 23c = 0 + -14 Combine like terms: 0 + -14 = -14 23c = -14 Divide each side by '23'. c = -0.6086956522 Simplifying c = -0.6086956522
| 4x-3=4x-5 | | 7.2x+2=6.2x | | 15f=k(k-f)+7+8f | | 1x+45=2x-2 | | (40x+16/6)/(20x+8/6x) | | 88=n+81 | | u+32=99 | | 0.091=1-z | | -20p+10=-19p-19 | | y^8*y^15= | | 7q=84 | | 4.7d=6.11 | | -20p+10p=-19p-19 | | 5.6-0.32s=1.12 | | 16.15=w+3 | | y+3.33=14.33 | | 208-3x=(x+1)+(x+2)+(x+3)-50 | | 10*0.32-5.6=1.12 | | -4+4=-29 | | 7=3.14+x | | 7=3.14 | | 7x^3+20x^2-32x=0 | | 208-3x=(x+1)+(x+2)+(x+3)+(x+4)-50 | | 8x+8=5x+5 | | 12x+8=90 | | 3+x=3-x | | 9x=15+3x | | 3y+15=4y-20 | | 2x+3(4x+2)=34 | | 28=6g-8 | | 2x-20=x/2+10 | | 48x^3-12x^2-6x=0 |